2009
DOI: 10.1111/j.1440-1819.2009.01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts in adult patients with idiopathic generalized epilepsy

Abstract: Aims:To study clinical features of adult patients with idiopathic generalized epilepsy with special attention to suicidal behavior. Methods:We reviewed the medical records of 145 consecutive adult patients with electro-clinically confirmed idiopathic generalized epilepsy and identified those with a history of at least one attempted suicide. Clinical variables in relation to their epilepsy and psychiatric conditions were analyzed.Results: Seven patients (4.8%) had a history of suicide attempts with drug overdos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
(29 reference statements)
3
15
0
1
Order By: Relevance
“…Epilepsy affects physical, mental and behavioral functions and is associated with higher risk of premature death due to traumatic brain injury [3], [4], status epilepticus, suicide, pneumonia and sudden death, and it accounts for 1.4% of all years of life lost [5], [6]. A study found 4.8% of patients with idiopathic generalized epilepsy (IGE) had attempted suicide, a much higher rate than that of the general population [7][9]. These suicidal patients were diagnosed with one or more psychiatric disorders [7].…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy affects physical, mental and behavioral functions and is associated with higher risk of premature death due to traumatic brain injury [3], [4], status epilepticus, suicide, pneumonia and sudden death, and it accounts for 1.4% of all years of life lost [5], [6]. A study found 4.8% of patients with idiopathic generalized epilepsy (IGE) had attempted suicide, a much higher rate than that of the general population [7][9]. These suicidal patients were diagnosed with one or more psychiatric disorders [7].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis seems to be supported by epidemiological data suggesting that people with a history of suicidal behavior have a fivefold higher risk of developing epilepsy [34]. Results about epilepsy-related variables are, however, still contradictory [35]. What is already established is that, in some selected cases, intense suicidal ideation can occur as a post-ictal event.…”
Section: Suicide In Epilepsymentioning
confidence: 93%
“…Some authors have suggested that the rate of suicide is higher in people with temporal lobe epilepsy 15. Idiopathic generalized epilepsy has recently been studied with both retrospective and prospective methods in 145 consecutive adults 19. No epilepsy-related factors were associated with suicide attempts while all index cases had a current psychiatric disorder (mood disorders, neurotic disorders, or personality disorders) and psychosocial events were considerably relevant.…”
Section: Epilepsy Depression and Suicide: What Is The Role Of Aeds?mentioning
confidence: 99%